Penerapan Metode Bercerita menggunakan Boneka Tangan dalam Meningkatkan Kemampuan Menyimak pada Anak Kelompok A2 TK Aisyiyah 1 Tolitoli - Datuamas, Kartini (Bahasantodea, 2016)
The problem statement in this research is lack of the scrutinizing ability of the A2 group children at TK Aisyah 1 Toli-toli. This research has the purpose for improving scrutinizing ability of the children through telling method in A2 group at TK Aisyah 1 Toli-toli, which have 18 children, they are consist of 8 boys children and 10 girls children which registered at the year 2015/2016. This research used kemmis research design and Mc. Taggart, which consist of 2 cycles, where at the every cycle implemented once meeting in the class and every cycle has 4 steps, there are planning, implementing, observation and reflection. The collected data through observation technique, giving the task, and documentation. Then, the data analyzed by descriptive from qualitative and quantitative data. Based on the data and the research outcomes at every cycle which has done in the A2 group at TK Aisyah 1 Toli-toli, there is able to take the conclude that : to improve scrutinizing children ability, so it did the repair with apply telling method using hand doll and in this research the kinds of the hand doll used base on the the children happiness and suitable with the learning topic. The telling method with using hand doll, it did a collaboration with the classmate to resulting the data and observation outcomes which will support to see the outcome of development. Children scrutinize ability of the A2 group at TK Aisyah 1 Toli-toli after applied the telling method using hand doll there is a signifigance chance. At the cycle (I), children scrutinize ability is less from 80%, and after did a repair, the children scruitinize ability to be close from the outcome which very well, with there is a oral language communication between the children and the teacher in learning process. At the cycle (II) action, the children scrutinize ability more than 80%. This is show that the application telling method using hand doll can improve the children scrutinize ability of the A2 group at TK Aisyah 1 Toli-toli.